Light-cured epoxy ink with low refractive index for display packaging as well as preparation method and application of light-cured epoxy ink
By introducing low refractive index components such as fluorine-substituted epoxy monomers into the packaging materials of OLED display devices, a low refractive index photocurable epoxy ink was prepared, which solved the problem of low light extraction efficiency of OLED display devices, achieving higher light extraction efficiency and longer device life.
Patent Information
- Application Number
- CN202510000320.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-22
AI Technical Summary
The light extraction efficiency of existing OLED display devices is low, resulting in high energy consumption and poor display effect, and the refractive index of the packaging materials is too high, affecting the low loss requirements of light.
A photocurable epoxy ink with low refractive index was developed, and ink with low refractive index and excellent aging resistance and bending properties were prepared by introducing fluorine-substituted epoxy monomers, alicyclic epoxy monomers and oxetane compounds into the epoxy ink, combined with photoinitiators and additives.
It improves the light extraction efficiency of OLED, extends the device life and stability, and reduces the refractive index of the material, meeting the requirements of semiconductor devices for low light loss.
Smart Images

Figure BDA0005224787540000031 
Figure BDA0005224787540000032 
Figure BDA0005224787540000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of OLED display packaging, and in particular relates to a light-curing epoxy ink with a low refractive index for display packaging, and a preparation method and application thereof. Background Art
[0002] OLED (Organic Light-Emitting Diode), also known as organic electroluminescent device, has become the mainstream display technology in the field of consumer electronics. Organic light-emitting diodes (OLED) have become the mainstream display technology in the field of consumer electronics. Some of the characteristics of OLED displays are spontaneous luminescence, transparency, true dark tones and good flexibility. Compared with liquid crystal displays, it has superior performance. Especially compared with printing and vacuum evaporation technology, the printing method has high material utilization rate, low cost, does not require harsh preparation conditions, and is easy to manufacture on a large scale. OLED has great application potential in the fields of commerce, medicine, education, etc.
[0003] At present, OLED display devices still have the limitation of low service life in application. The main reason for the loss is that the moisture and dust in the use environment damage the light-emitting layer after contacting it, which is manifested as black spots on the light-emitting layer. In severe cases, it will cause a black screen that cannot be used. Therefore, using reliable packaging materials to protect the light-emitting layer is the most efficient solution at present, which puts higher requirements on the barrier property and reliability of the packaging layer. The thin-film packaging process currently used mainly adopts a sandwich structure, with an inorganic layer with extremely high water-proof properties on the outer layer and an organic layer in the middle. Its main function is to prevent the inorganic layer from being damaged due to mechanical stress. In addition, the current development of flexible OLEDs has put forward new requirements for the flexibility of materials, requiring materials to have better bending resistance.
[0004] At the same time, although OLED technology is widely used in the fields of display and lighting, there is still a bottleneck in light extraction efficiency, which has great limitations on the energy consumption of materials and display effects. Currently, most research is focused on the inside of OLED devices, and there is very little research on the external encapsulation layer. Literature shows that by reducing the refractive index of the organic layer to that of air, the light extraction efficiency of both bottom-emitting OLEDs and top-emitting OLEDs can be increased to 70%.
[0005] CN113004808A discloses a synthesis of a low-refractive-index organic compound, which mainly uses a combination of multiple conjugated aromatic rings to reduce the refractive index of the material. However, its refractive index is still greater than 1.5, and the evaporation process is used, which greatly increases the application cost.
[0006] CN 113841263 A discloses a moisture barrier film with low refractive index and low water vapor permeability for an organic light emitting diode device, but the patent is only applicable to the inorganic layer in the encapsulation layer, and the refractive index is not significantly reduced, being only 1.46.
[0007] Since the refractive index of the currently used epoxy encapsulation composition is above 1.5, it has a great impact on the light extraction efficiency of OLED and is difficult to meet the requirements of semiconductor devices for low light loss. The currently disclosed low-refractive-index encapsulation compositions still have various problems and cannot meet the actual application requirements.
[0008] Therefore, it is necessary to develop a photocurable composition that has good reliability and meets the low refractive index performance requirements and is suitable for thin film encapsulation technology to solve the above technical problems. Summary of the invention
[0009] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a photocurable epoxy ink with a low refractive index that can be used in printing processes. The photocurable epoxy ink has a low refractive index, excellent aging resistance and bending properties, so that when it is used in display devices, it can effectively improve the light extraction efficiency and extend the life and stability of the device.
[0010] Another object of the present invention is to provide a preparation method and application of the photocurable epoxy ink.
[0011] To achieve this object, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides a low-refractive-index photocurable epoxy ink for display packaging, wherein the photocurable epoxy ink comprises the following components in parts by weight:
[0013]
[0014] The fluorine-substituted epoxy monomer is selected from one or more of alicyclic, aromatic and aliphatic epoxy monomers containing fluorine substitution in the molecule.
[0015] In a specific embodiment, the fluorine-substituted epoxy monomer is synthesized by reacting an olefin containing fluorine in the molecule with m-chloroperbenzoic acid or hydrogen peroxide;
[0016] In a preferred embodiment, the fluorine-substituted epoxy monomer has a structure shown in the following formula (I):
[0017]
[0018] Wherein, R1 is a hydrogen atom or a methyl group;
[0019] R2 is a hydrogen atom, a fluorine atom, or an aliphatic alkyl group having less than 6 carbon atoms;
[0020] R3 represents a fluorine-substituted aliphatic alkyl group, aromatic alkyl group, alicyclic group or heterocyclic alkyl group.
[0021] Specifically, the alkyl or heterocycloalkyl group includes C2-12 alkyl, C6-C12 aryl, C3-C10 cycloalkyl, and specifically includes but is not limited to one or two or more of phenyl, biphenyl, cyclobutane, oxetanyl, cyclopentane, and cyclohexane.
[0022] In a specific embodiment, the fluorine-substituted group in the fluorine-substituted epoxy monomer is any one of a fluorine atom, a difluoromethyl group, a trifluoromethyl group, and a C2-C9 perfluorinated or partially fluorinated alkyl group.
[0023] In a preferred embodiment, the fluorine-substituted epoxy monomer is selected from at least one of the structural compounds represented by the following formulas 1 to 9:
[0024]
[0025] In the present invention, the amount of fluorine-substituted epoxy monomer is 30 to 60 parts by weight, for example, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59 parts by weight, etc., preferably 30 to 50 parts by weight; from the perspective of lowering the refractive index, the preferred lower limit of the amount of fluorine-substituted epoxy resin monomer is 30 parts by weight, and the preferred upper limit is 60 parts by weight. From the perspective of printing technology, the more preferred upper limit of the amount of fluorine-substituted epoxy monomer is 50 parts by weight.
[0026] In a specific embodiment, the alicyclic epoxy monomer is at least one of the epoxy compounds containing a single or multiple epoxy cyclohexane in the structural formula; preferably, the alicyclic epoxy monomer is an oxidized cycloolefin type alicyclic epoxy compound, specifically, for example, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, di-4-epoxycyclohexane, dicyclopentadiene epoxide, 2,2-bis(3,3'-epoxycyclohexyl)propane, di-7-oxabicyclo[4,1,0]heptane, 1,2:5,6-diepoxyhexahydroindane, etc. Among them, from the perspective of curing rate and viscosity, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate is preferred.
[0027] In the present invention, the amount of the alicyclic epoxy monomer is 10 to 40 parts by weight, for example, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39 parts by weight, preferably 10 to 30 parts by weight. From the perspective of improving reliability, the preferred lower limit of the amount of the alicyclic epoxy monomer is 10 parts by weight, and the preferred upper limit is 40 parts by weight. From the perspective of bending resistance, the more preferred upper limit of the amount of the alicyclic epoxy monomer is 30 parts by weight.
[0028] In a specific embodiment, the oxetane monomer comprises at least one of a monofunctional oxetane compound and a multifunctional oxetane compound. The monofunctional oxetane compound is, for example, 3-ethyl-3-((2-ethylhexyloxy)methyl)oxetane, phenoxymethyloxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(phenoxymethyl)oxetane, 3-allyloxyoxetane, 3-ethyl-3-allyloxyoxetane, 3-ethyl-3-acryloyloxymethyloxetane, 2-methyl-2-allyl-4-propyloxetane, etc. any one of the multifunctional oxetane compounds such as 3-ethyl-3-(((3-ethyloxetane-3-yl)methoxy)methyl)oxetane, xylene dioxetane, phenol novolac type oxetane, oxetane silsesquioxane, 1,4-bis((3-ethyl-3-oxetane methoxy)methyl)benzene, bis((3-methyl-3-oxetane methoxy)methyl)ether, and bis((3-ethyl-3-oxetane methoxy)methyl)ether.
[0029] In the present invention, the amount of the oxetane monomer is 10 to 40 parts by weight, for example, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 parts by weight, preferably 10 to 30 parts by weight. From the perspective of improving the printing effect, the amount of the oxetane compound is preferably limited to 10 parts by weight and preferably limited to 30 parts by weight. From the perspective of improving the curing efficiency, the amount of the oxetane compound is more preferably limited to 20 parts by weight and more preferably limited to 30 parts by weight.
[0030] In a specific embodiment, the diluent comprises at least one of an aliphatic glycidyl ether compound and a vinyl ether compound. The aliphatic glycidyl ether compound includes, for example, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polypropylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, glycerol triglycidyl ether, butyl glycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, trimethylolethane triglycidyl ether, and the like; and a vinyl ether compound includes, for example, one or more of benzyl vinyl ether, cyclohexanedimethanol monovinyl ether, dicyclopentadiene vinyl ether, 1,4-butanediol divinyl ether, cyclohexanedimethanol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, and the like.
[0031] In the present invention, the amount of the diluent is 10 to 40 parts by weight, for example, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 parts by weight, preferably 10 to 30 parts by weight. From the perspective of improving the printing effect, the preferred lower limit of the amount of the diluent is 10 parts by weight, and the preferred upper limit is 40 parts by weight. From the perspective of suppressing the volatile content, the more preferred upper limit of the amount of the diluent is 30 parts by weight.
[0032] In a specific embodiment, the photoinitiator is a cationic photoinitiator, preferably selected from at least one of aromatic sulfonium salts, aromatic iodonium salts, aromatic diazonium salts, aromatic ammonium salts, and ferrocenium salts. Specifically, the initiator applicable to the present composition may include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, cumylcyclopentadienyl iron hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, etc.
[0033] In the present invention, the amount of the photoinitiator is 0.5 to 5 parts by weight, for example 0.6, 0.8, 1.0, 1.5, 2.0, 2.5, 2.5, 3.0, 3.5, 4.0, 4.5, 5 parts by weight, preferably 0.5 to 2 parts by weight. From the perspective of improving the curing effect, the amount of the photocationic initiator is preferably limited to 0.5 parts by weight, and the upper limit is preferably 5 parts by weight. From the perspective of improving storage stability, the amount of the photoinitiator is more preferably limited to 0.1 parts by weight, and the upper limit is more preferably 2 parts by weight.
[0034] In a specific embodiment, the auxiliary agent mainly comprises a sensitizer, one or any combination of a surfactant, a defoamer, a dispersant, a leveling agent, a coupling agent, and a stabilizer. Specifically, sensitizers such as thioxanthone compounds, 2,2-dimethoxy-1,2-diphenylethane-1-one, benzophenone, 2,4-dichlorobenzophenone, methyl o-benzoylbenzoate, 4,4'-bis(dimethylamino)benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, and 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-isocyanatepropyltrimethoxysilane coupling agents can be cited.
[0035] In the present invention, the auxiliary agent may be added or not added, and the added amount is 0 to 2 parts by weight, for example, 0, 0.5, 1, 1.5, 2 parts by weight, etc.
[0036] Another aspect of the present invention is a method for preparing a low-refractive-index photocurable epoxy ink for display packaging, comprising the following steps:
[0037] A certain weight portion of fluorine-substituted epoxy monomer, alicyclic epoxy monomer, oxetane compound, diluent, photoinitiator and optional auxiliary agent are added to a reaction kettle, and the temperature is maintained at 20-30° C. and stirred for 20-40 minutes to mix the composition evenly to obtain the photocurable epoxy ink composition with a viscosity between 10-30 cps.
[0038] On the other hand, the aforementioned low-refractive-index photocurable epoxy ink for display encapsulation or the low-refractive-index photocurable epoxy ink for display encapsulation prepared by the aforementioned preparation method is used in an inkjet printing process in the field of display encapsulation.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The photocurable epoxy ink composition of the present invention comprises alicyclic epoxy monomers, diluents, fluorine-substituted epoxy monomers, photoinitiators and additives. Since the introduced fluorine atoms have high electronegativity and low polarizability, the refractive index of the material can be effectively reduced, thereby improving the light extraction efficiency of OLED. Compared with hydrocarbons, fluorine-containing polymers have higher thermal stability and better chemical resistance.
[0041] The light-curing epoxy ink packaging composition prepared by the present invention can have good reliability performance and low refractive index. DETAILED DESCRIPTION
[0042] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions therein are essentially used as illustrations rather than to limit the present invention.
[0043]
[0044] Synthesis route of m-chlorobenzoic acid
[0045] Sources of raw materials needed for synthesis
[0046]
[0047] Preparation Example
[0048] Preparation of product of formula 1:
[0049] Weigh 0.16 mol of m-chloroperbenzoic acid (MCPBA) and add it to a three-necked flask equipped with a stirrer, a heating jacket and a condenser. Dilute 0.05 mol of [(1S)-1-fluoroprop-2-enyl] cyclohexane with dichloromethane solvent and then add it to the three-necked flask; stir and heat to 30°C. Reflux reaction for 25 hours. After the reaction is completed, cool to room temperature and stir for 2 hours to allow the unreacted MCPBA to fully precipitate. Filter the product with a G3 sand core funnel, extract it with a saturated sodium sulfite ice water solution and a 5wt% NaHCO3 solution for multiple times, and finally wash the dichloromethane layer with a 3wt% NaCl solution; extract and purify the oil phase and concentrate it by rotary evaporation, and vacuum dry it to obtain the target product with a yield of 83%.
[0050] 1 H NMR (500MHz, CDCl3) δ7.31 (t, J = 13.1Hz, 4H), 6.91 (d, J = 9.0Hz, 4H), 1.23-1.64 (10H, J = 13.3, 2. 8Hz)), 1.86 (1H, J=10.3, 2.8Hz), 2.96-3.19 (3H, J=8.1, 7.7, 4.2Hz)), 4.47 (1H, J=4.7, 4.3Hz).
[0051] Preparation of product of formula 2:
[0052] Weigh 0.16 mol of m-chloroperbenzoic acid (MCPBA) and add it to a three-necked flask equipped with a stirrer, a heating jacket and a condensing device. Dilute 0.05 mol of 6-fluoro-6-methyl-1-heptene with a solvent of dichloromethane and then add it to the three-necked flask; stir and heat to 30°C. Reflux reaction for 25 hours. After the reaction is completed, cool to room temperature and stir for 2 hours to allow the unreacted MCPBA to fully precipitate. Filter the product with a G3 sand core funnel, extract it with a saturated sodium sulfite ice water solution and a 5wt% NaHCO3 solution for multiple times, and finally wash the dichloromethane layer with a 3wt% NaCl solution; extract and purify the oil phase and concentrate it by rotary evaporation, and vacuum dry it to obtain the target product with a yield of 78%.
[0053] 1 H NMR(500MHz, CDCl3)δ7.31(t,J=13.1Hz,4H),6.91(d,J=9.0Hz,4H),1.19-1.29(6H,1.24(s) ,1.24(s)),1.38-1.64(6H,J=7.5,7.4,5.4Hz)),2.97-3.15(3H,3.04(J=8.1,7.7,5.4Hz)).
[0054] Preparation of Formula 6 product:
[0055] Weigh 0.16 mol of m-chloroperbenzoic acid (MCPBA) and add it to a three-necked flask equipped with a stirrer, a heating jacket and a condenser. Dilute 0.05 mol of 11-fluoro-1-undecene with a solvent of dichloromethane and then add it to the three-necked flask; stir and heat to 30°C. Reflux reaction for 25 hours. After the reaction is completed, cool to room temperature and stir for 2 hours to allow the unreacted MCPBA to fully precipitate. Filter the product with a G3 sand core funnel, extract it with a saturated sodium sulfite ice water solution and a 5wt% NaHCO3 solution for multiple times, and finally wash the dichloromethane layer with a 3wt% NaCl solution; extract and purify the oil phase by rotary evaporation and vacuum drying to obtain the target product with a yield of 80%.
[0056] 1 H NMR (500MHz, CDCl3) δ7.31(t,J=13.1Hz,4H),6.91(d,J=9.0Hz,4H),1.15-1.60(67H,1.23(J=7.00,7.10,7.24,5.40Hz)),1. 70-1.87(9H,J=7.50,7.50,6.93,6.93Hz)), 2.97-3.15(14H,J=8.06,7.69,5.40,5.40Hz), 4.11-4.25(10H,J=6.93,6.93Hz).
[0057] Preparation of product of formula 7:
[0058] Weigh 0.16 mol of m-chloroperbenzoic acid (MCPBA) and add it to a three-necked flask equipped with a stirrer, a heating jacket and a condenser. Dilute 0.05 mol of 4,4-bis(fluoromethyl)-1-hexene with a solvent of dichloromethane and then add it to the three-necked flask; stir and heat to 30°C. Reflux reaction for 25 hours. After the reaction is completed, cool to room temperature and stir for 2 hours to allow the unreacted MCPBA to fully precipitate. Filter the product with a G3 sand core funnel, extract it with a saturated sodium sulfite ice water solution and a 5wt% NaHCO3 solution for multiple times, and finally wash the dichloromethane layer with a 3wt% NaCl solution; extract and purify the oil phase, concentrate it by rotary evaporation, and vacuum dry it to obtain the target product with a yield of 75%.
[0059] 1 H NMR (500MHz, CDCl3) δ7.31 (t, J = 13.1Hz, 4H), 6.91 (d, J = 9.0Hz, 4H), 1.47-1.59 (2H, J = 5.4, 3. 4Hz), 2.27 (1H, J=3.4, 3.3Hz), 2.99-3.21 (3H, J=8.1, 7.7, 5.4Hz)), 4.05-4.15 (4H, J=3.3Hz).
[0060] Preparation of Formula 9 product:
[0061] In a three-necked flask equipped with a stirrer, a heating jacket and a condensing device, 0.05 mol of heptafluoropentene-1 and chloroform solvent were added, a certain amount of phosphotungstic acid and a phase transfer catalyst methyltrioctylammonium chloride were taken, the temperature was raised to 50°C, and 0.22 mol of hydrogen peroxide was taken to react at a constant temperature for 9 hours. After the reaction was completed, the stirring was stopped, the mixture was cooled to room temperature, and the mixture was separated by extraction with distilled water. The chloroform layer was washed with water until it was neutral, and then anhydrous Na2SO4 was added to dry it, filtered, and the solvent was removed by rotary evaporation. The target product was obtained by drying with a yield of 73%.
[0062] 1 H NMR (500MHz, CDCl3) δ7.31 (t, J = 13.1Hz, 4H), 6.91 (d, J = 9.0Hz, 4H), 2.93-3.14 (3H, J = 8.1, 7.7, 4.3Hz).
[0063] Sample Example:
[0064] Ingredients:
[0065] A Cycloaliphatic Epoxy Resin:
[0066] A1: Bis-7-oxabicyclo[4,1,0]heptane (purchased from Daicel Japan)
[0067] A2: 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate (purchased from Nantong Xinnaxi); B: fluorine-substituted epoxy resin:
[0068] B1: the compound represented by formula 1;
[0069] B2: the compound represented by formula 2;
[0070] B3: the compound represented by formula 6;
[0071] B4: the compound represented by formula 7;
[0072] B5: the compound represented by formula 9;
[0073] B6: hexafluoropropylene trimer-based bisphenol A epoxy resin monomer (2994-63-0, purchased from Shanghai Titan); C: oxetane compound:
[0074] C1: 3-ethyl-3-oxetane methanol (purchased from Donghua New Materials);
[0075] C2: 3,3'-[oxybismethylene]bis[3-ethyl]oxetane (purchased from Donghua New Materials);
[0076] DDiluent:
[0077] D1: 1,4-butanediol diglycidyl ether (purchased from Aladdin Reagent);
[0078] D2: dicyclopentadiene vinyl ether (purchased from Aladdin Reagents)
[0079] E Cationic photoinitiator:
[0080] E1: UVI-6976 (purchased from Donghua New Materials);
[0081] F additives:
[0082] F1: Sensitizer TR-PSS-510 (purchased from Qiangli New Materials)
[0083] Example 1
[0084] 20 parts by weight of bis-7-oxabicyclo[4,1,0]heptane, 40 parts by weight of the compound represented by formula 1, 20 parts by weight of 3,3'-[oxybismethylene]bis[3-ethyl]oxetane and 20 parts by weight of 1,4-butanediol diglycidyl ether, 1 part by weight of initiator UVI-6976 and 0.1 part by weight of sensitizer TR-PSS-510 were put into a reaction kettle, and the mixture was stirred at 60 r / min for 20-40 minutes while keeping the temperature at 20-30° C. under light-proof conditions to make the composition evenly mixed.
[0085] According to the preparation method of Example 1, Examples 2-6 and Comparative Examples 1-3 were prepared with the weight parts described in Table 1.
[0086] Table 1 Weight ratio of each component (parts by weight)
[0087]
[0088]
[0089] Performance Testing
[0090] 1) Sample viscosity
[0091] The samples were added into the rheometer and the viscosity of each composition was tested at 25°C.
[0092] 2) Curing rate
[0093] The composition was evenly coated on a glass substrate and a UV-LED light source with a wavelength of 395 nm was used with a curing energy of 1500 mJ / cm 2 A film with a thickness of 12 μm was prepared, and the infrared spectra of each composition before and after curing were tested using an FT-IR device (Nicolet iS5 of Thermo Fisher Scientific). The infrared spectra of the composition before and after curing at 980 cm -1 and 2862cm -1 The intensity of the absorption peak of the nearby cured film is calculated by the following formula:
[0094] Photocuring rate (%) = |1-(A / B)| × 100%
[0095] Where A represents the cured film at 980cm -1 and 2862cm -1 The intensity ratio of the absorption peaks near 980cm -1 and 2862cm -1 The intensity ratio of nearby absorption peaks.
[0096] 3) Transmittance
[0097] The composition was uniformly coated on a glass substrate, and a 12 μm thick film was prepared using a UV-LED light source in the 395 nm band and a curing energy of 1500 mJ / cm2. The light transmittance of each sample was tested using a colorimeter (HunterLab UltraScan VIS).
[0098] 4) Reliability test
[0099] The composition is uniformly coated on a surface containing SiN xOn the coated glass substrate, a UV-LED light source with a wavelength of 395nm was used, and the curing energy was 1500mJ / cm 2 The film with a thickness of 12 μm was placed in an environment of 85°C and 85% Rh for 500 hours, and there was no peeling or damage on the surface. Indicates that the surface is damaged. express.
[0100] 5) Bending test
[0101] The composition was evenly coated on the PI film and a UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The flexural properties of the PI film plus the composite film were tested at -20°C using a flexural tester (IR = 2.0), and the film that passed 200,000 flexural tests was recorded as , those that fail the 200,000 bending test are recorded as
[0102] 6) Refractive index test
[0103] The composition was evenly coated on a glass substrate and a UV-LED lamp with a wavelength of 395 nm was used to apply 1500 mJ / cm 2 The energy was cured into a 12μm film, and the refractive index of the film was tested using an ellipsometer M-2000v.
[0104] 7) Inkjet performance test
[0105] The inkjet printing performance of each composition was tested by a piezoelectric drop-on-demand print head (KM1024i Konica Minolta). Using an inkjet head temperature of 25°C, 4 μm and 10 μm films were printed on SiNx substrates, and the film surface was observed by OM microscopy. Indicates that the surface has defects or cannot form a film express.
[0106] The performance test results are shown in the following table:
[0107]
[0108]
[0109] It can be seen from the performance test data results in the table that the photocurable compositions prepared in Examples 1-6 have a lower refractive index than the comparative examples, and it can be seen from Comparative Example 2 that the fluorine-containing resin used in the examples is more suitable for inkjet printing process than commercially available products; it can be seen from the comparative examples and examples that after introducing a suitable amount of fluorine-containing monomers, the reliability of the curable compositions is also improved.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A low refractive index photocurable epoxy ink for display packaging, characterized in that: The photocurable epoxy ink comprises the following components in parts by weight: The fluorine-substituted epoxy monomer is selected from one or more of alicyclic, aromatic and aliphatic epoxy monomers containing fluorine substitution in the molecule.
2. The light-curing epoxy ink according to claim 1, characterized in that: The fluorine-substituted epoxy monomer is synthesized by reacting an olefin containing fluorine in the molecule with m-chloroperbenzoic acid or hydrogen peroxide; Preferably, the fluorine-substituted epoxy monomer has a structure as shown in the following formula (I): Wherein, R1 is a hydrogen atom or a methyl group; R2 is a hydrogen atom, a fluorine atom, or an aliphatic alkyl group having less than 6 carbon atoms; R3 represents a fluorine-substituted C1-C12 aliphatic alkyl group, an aromatic alkyl group having two or fewer aromatic rings, or an alkyl group consisting of an alicyclic ring or a heterocyclic ring.
3. The light-curing epoxy ink according to claim 2, characterized in that: The fluorine-substituted group in the fluorine-substituted epoxy monomer is any one of a fluorine atom, a difluoromethyl group, a trifluoromethyl group, a C2-C9 perfluorinated or partially fluorinated alkyl group; Preferably, the fluorine-substituted epoxy monomer is selected from at least one of the structural compounds represented by the following formulas 1 to 9:
4. The light-curing epoxy ink according to claim 1, characterized in that: The alicyclic epoxy monomer is at least one of single or multiple epoxy cyclohexane epoxy compounds in the structural formula; preferably, the alicyclic epoxy monomer is at least one of oxidized cycloolefin type alicyclic epoxy compounds; more preferably, it is 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate.
5. The light-curing epoxy ink according to claim 1, characterized in that: The diluent comprises at least one of an aliphatic glycidyl ether compound and a vinyl ether compound.
6. The light-curable epoxy ink according to claim 1, characterized in that: The oxetane monomer includes at least one of a monofunctional oxetane compound and a multifunctional oxetane compound.
7. The light-curable epoxy ink according to claim 1, characterized in that: The photoinitiator is a cationic photoinitiator, and is preferably selected from at least one of aromatic sulfonium salts, aromatic iodonium salts, aromatic diazonium salts, aromatic ammonium salts, and ferrocenium salts.
8. The light-curable epoxy ink according to claim 1, characterized in that: The auxiliary agent comprises at least one of a photosensitizer, a surfactant, a defoamer, a dispersant, and a leveling agent.
9. The method for preparing the low-refractive-index photocurable epoxy ink for display packaging according to any one of claims 1 to 8, characterized in that: The steps include: Adding alicyclic epoxy monomer, fluorine-substituted epoxy monomer, oxetane monomer, diluent, photoinitiator and optional auxiliary agent into a reaction kettle, stirring under light-proof conditions to make various components uniformly mixed, to obtain the light-curing epoxy ink; Preferably, the stirring temperature is 20-30°C, and the stirring time is 20-40 min.
10. Use of the low-refractive-index photocurable epoxy ink for display encapsulation according to any one of claims 1 to 8 or the low-refractive-index photocurable epoxy ink for display encapsulation prepared by the preparation method according to claim 9 in an inkjet printing process for display encapsulation.
Citation Information
Patent Citations
Low-dielectric-coefficient ultraviolet curing adhesive as well as use method and application thereof
CN113004808A
Moisture barrier film having low refraction index and low water vapor tramission rate
CN113841263A